PENGARUH GAYA HIDUP, TEMAN SEBAYA DAN LITERASI KEUANGAN TERHADAP PERILAKU KONSUMTIF: (Survei pada Mahasiswa Pendidikan Ekonomi Universitas Siliwangi Angkatan 2020) - Yovi Fujinauri; Iis Aisyah; Rendra Gumilar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research was motivated by problems that occurred among students of the 2020 Economic Education study program, Faculty of Teacher Training and Education, Siliwangi Tasikmalaya University, namely regarding consumer behavior. The aim of carrying out this research is to determine the extent of the influence of lifestyle, peers and financial literacy on consumer behavior in economics education students class of 2020, both simultaneously and partially. This research uses a quantitative survey type research method with a design, namely an explanatory survey. The population in this study were all students from the Department of Economic Education, Siliwangi University Class of 2020. The sampling technique used was nonprobability sampling, namely saturated sampling, totaling 115 students. The data collection technique uses a questionnaire with multiple linear data regression analysis techniques using the SPSS 16.0 for Windows program. The research results show that: 1) There is a significant influence of lifestyle on consumer behavior with a value of tcount > ttable (6.787 > 1.981). 2) There is a significant influence from peers on consumer behavior with a value of tcount > ttable (7.380 > 1.981). 3) There is a significant influence of financial literacy on consumer behavior with a value of tcount > ttable (4.062 > 1.981).